Chronic exposure to low intensity natural light blocks spawning in the cichlid fish Oreochromis mossambicus - C.B. Ganesh; V.R. Mokashi (Journal of Basic and Applied Zoology, 2015)
The tilapia Oreochromis mossambicus shows a series of short ovarian cycles throughout the year. The present study examined the impact of low intensity ambient natural light (ANL) in indoor environment on the follicular developmental status and the spawning cycle of O. mossambicus. The stripped fish (eggs removed manually, day 1) held outdoors in direct natural light (DNL) successfully spawned between 24 and 28 days, whereas those reared in ANL failed to spawn despite the presence of a significantly higher number of stage V (vitellogenic) follicles in the ovary compared to that of DNL during the prespawning phase (day 23). These fish did not spawn even up to day 50. The profile of serum levels of cortisol did not show a significant difference between the two experimental conditions. On the other hand, the serum levels of estradiol (E2) were significantly higher during vitellogenic phase (day 18) compared to previtellogenic phase (day 12) in both experimental fish. In fish exposed to DNL, the serum levels of E2 decreased prior to spawning, but remained significantly higher in fish exposed to ANL, suggesting the possible absence of a steroidogenic shift prior to spawning. The results reveal that lack of a critical environmental cue such as the light signal might affect the spawning cycle by causing alterations in the ovarian steroidogenic activity, for the first time in a continuously breeding fish such as O. mossambicus.